Dąbrowszczacy i pamięć o hiszpańskiej wojnie domowej w Polsce Ludowej - Różycki, Bartłomiej (Pamięć i Sprawiedliwość, 2013)
The Spanish Civil War attracted thousands of volunteers from various countries to fight on the Republican side. There were over 5000 Poles among them, although a vast part of them came not directly from Poland, but from economic migration, mostly in France. Their common designation – “Dąbrowszczacy”, comes from the name of the patron of the most important military unit they belonged to: a hero of Polish 19 th century independence struggles, Jarosław Dąbrowski. Analogously to the volunteers from other countries, most of them originated from working-class and were related to communist ideology. They were all deprived of Polish citizenship, in accordance to the law that forbid serving for a foreign army. A Pole who gained the most fame in Spain was Karol Świerczewski, “Walter”, who was also a general of Soviet army.In the postwar, communist Poland, the “Dąbrowszczacy” not only retrieved citizenship, but also gained various privileges. They were used by propaganda as an example of “correct” attitude: combined patriotism with proletarian interna-tionalism. It was argued that their actions in Spain had been a conscious effort to push aside danger of fascist aggression towards Poland, that finally happened in 1939. Many veterans fulfilled responsible tasks for the machinery of the totalitarian state. They also conducted aid for their former brothers in arms, as well as acts of solidarity with anti-franquist opposition, especially with Spanish communists. At first, all their activities were run through their own association (“Związek Dąbrowszczaków”), and later in ZBoWiD – a huge organization that combined all veteran groups approved by the authorities.Nonetheless, the veterans of Spanish war were not immune to suppressions, which according to the logic of communist dictatorship were extended even on those in power. Some of them were imprisoned during the Stalinist period but released and vindicated afterwards. Those of Jewish origin were also suppressed during the anti-Semitic campaign of 1968. With the time passing, the position of this environment declined, although those still active in public live attempted to maintain the remembrance of their actions. Nowadays, in the democratic Poland, the discussion about their role in Spanish war and the communist regime still brings up many controversies.